APLIKASI EKSTRAK KULIT KAYU MANIS (Cinnamomum burmanii) UNTUK MENGHAMBAT AKTIVITAS BAKTERI IKAN LELE (Clarias batrachus) - Adolf Jan Nexson Parhusip; Lulu Julisa Cynthia (FaST : Jurnal Sains dan Teknologi, 2019)
Cinnamon bark (Cinnamomum burmanii) contains antibacterial compounds which are potential in inhibiting a series of pathogenic bacterial and also capable in inhibiting bacterial activity of food products. These compounds are alkaloid, saponin, tannin, phenolic, flavonoid, triterpenoid, and glycoside. This research was conducted through well-diffusion method to determine the antibacterial activities of cinnamon bark extract in inhibiting the growth of pathogenic bacteria such as, P. aeruginosa, S. Typhi, S. aureus, L. monocytogenes, E. coli, S. thermophilus and test the stability of cinnamon bark extract toward salt, sugar, pH, and heat. This research was also conducted to inhibit bacterial activity in catfish with the application of cinnamon bark extract. Cinnamon bark extract was concentrated to 5, 10, 15, and 20% for the well-diffusion method. The selected concentration was 5%, since it resulted in more than 10mm inhibitory diameter on every bacterial test. The selected extract concentration was proceeded to the stability test toward salt, sugar, pH, and heat. Results showed that cinnamon bark extract remained stable within 4% salt solution, 40% sugar solution, pH 4 solution, however it wasn’t stable through 100 0C heating for 15 minutes. The application of cinnamon bark extract on catfish was concentrated to 0MBC, 1MBC, 2MBC, 3MBC within 10, 20, and 30 minutes of immersion time. Results showed that the selected treatment was 3 MBC concentration within 30 minutes of immersion time, since it resulted in TVBN value (9,69±0,164 mgN/50g), TMA value (3,87±0,154 mgN/50g), TPC value (3,23x105 CFU/gram), and pH value (6,421±0,072). In addition, toxicity test was also performed to the selected cinnamon bark extract and it showed that cinnamon bark extract was toxic.